Green synthesis of submicron copper powder with narrow particle size distribution via a simple methanol thermal reduction. Issue 46 (17th November 2021) - Chen, Xiaoping; Fu, Jiaqi; Li, Jiangang; Chen, Bohong; Yang, Lei; Li, Zhichun
Abstract : Submicron copper powder with narrow particle size distribution was synthesized via a simple methanol thermal reduction with no organic product. Abstract : In this work, submicron copper powder with narrow particle size distribution was synthesized via a simple methanol thermal reduction method without using any surfactants. Smaller copper powder with narrower particle size distribution could be realized by increasing the reaction temperature. Submicron copper powder with an average particle size of 206.6 nm and a particle size distribution of 100–300 nm could be obtained when the reaction temperature was 200 °C. Methyl formate was the only organic product found in the reaction. No organic products could be realized when the reaction temperature increased to 180 °C and above, which was environmentally friendly and was conducive to the subsequent copper powder extraction and washing. The synthesis of submicron copper powder via methanol thermal reduction was found to be a top-down process, which was beneficial for ultrafine copper powder production via wet chemical approaches.